1996
DOI: 10.1093/qjmed/89.12.903
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of refractory Wegener's granulomatosis with humanized monoclonal antibodies

Abstract: Conventional immunosuppression for systemic vasculitides is limited by substantial side-effects, cumulative drug toxicity and refractoriness in some patients. Six Wegener's granulomatosis patients who had been refractory to conventional therapy for at least 6 months, were treated with humanized monoclonal antibodies specific to lymphocyte CD52 or CD4 antigens. Diagnosis was on clinicopathological grounds, supported by the presence of autoantibodies to Proteinase 3. Histological evidence of persistent disease a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
39
0
2

Year Published

1996
1996
2011
2011

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 106 publications
(42 citation statements)
references
References 13 publications
1
39
0
2
Order By: Relevance
“…Remission has been achieved using these agents in patients with resistant vasculitis, albeit with high relapse rates and a high rate of infectious complications (107)(108)(109).…”
Section: Treatment Of Patients With Asvmentioning
confidence: 99%
“…Remission has been achieved using these agents in patients with resistant vasculitis, albeit with high relapse rates and a high rate of infectious complications (107)(108)(109).…”
Section: Treatment Of Patients With Asvmentioning
confidence: 99%
“…A further report suggested that ATG may also be useful in patients with Wegener granulomatosis who are dialysis-dependent at diagnosis (56). Monoclonal anti-T cell antibodies have also shown sustained remission in small open studies (57). The use of these agents requires further study, but they do underline the importance of T cells in the pathogenesis of ANCA-associated vasculitis.…”
Section: Rescue Therapy For Refractory and Relapsing Diseasementioning
confidence: 99%
“…After its infusion, lymphocyte and monocytes counts fall rapidly over the first hour, and a prolonged period of lymphopenia ensues for over 2 yr. CAMPATH 1-H has been extensively used for the serotherapy of leukemias and lymphomas because of its ability to debulk circulating tumor cells (2,3), and to prevent renal allograft rejection (4). Recently CAMPATH 1-H has also found use in the treatment of autoimmune diseases, including rheumatoid arthritis (5) and vasculitis (6,7).…”
Section: Introductionmentioning
confidence: 99%